Industrial Sector Performance, Human Capital Development and Economic Growth in Nigeria - Adeosun, Theophilus Oluyemi; Odior, Simeon Ernest; Shittu, Ibrahim Ayodele; Adegbite, Waliu Mulero (Universitas Prasetiya Mulya, 2023)
This study examines the relationship between industrial sector performance (ISP), human capital development (HCD), and economicgrowth (EG) in Nigeria. Data used in this study was obtained from World Development Indicators (WDI) and Penn World from 1981 to 2020 on GDP/capita, human capital index, and industrial output. The augmented Dickey-Fuller (ADF) test was applied to obtain the stationarity conditions of the variables before performing the autoregressive distributed lag test to determine the short- and long-run relationships among the variables. The study reveals no long-run relationship among the variables; however, a negligible impact on human capital and industrial output in the short term exists, highlighting the need for government intervention. This is thefirst study to examine the tripartite relationship between industrial sector performance, human capital development, and economic growth in the Nigerian context, providing insight into the dynamics of the relationships in developing countries.